Analisis Gender terhadap Unsur Maskulinitas Pertimbangan Hakim dalam Perkara Penodaan Agama - Vivi Ariyanti (Equalita: Jurnal Studi Gender dan Anak, 2023)
This research departs from a paradigm that questions whether there is something about masculinity that influences the way judges decide cases in court. To do this, we conduct an assessment of the attitude of independence of judges from the factors that can influence court decisions, both internal factors from the judges themselves and external factors related to the interests of certain groups. Based on the discussion and analysis of several cases of blasphemy, this research concludes that the judges' decisions in blasphemy cases do not reflect the masculine values of the judges who decided the cases. A judge in making a decision must be based on the ability to think and will freely (independently) but within the limits of responsibility and objectivity. Decision making based on intuition or feelings has a subjective nature, so it is easy to be influenced. The results of the analysis of decisions confirm that judges' decisions in several cases of blasphemy are more influenced by elements outside the court, both in the form of mass pressure and fatwas of religious institutions that have no legal force. The nature of masculinity that tends to be analytical and breaks down everything to examine the parts carefully is actually abandoned. The panel of judges tends to take advantage of femininity, namely having a style that is more comprehensive and more situation oriented.